Development and evaluation of an online cardiotocography course tailored to LMIC settings: a feasibility study conducted in a tertiary care hospital in Sri Lanka - M. Rishard; I. Weerasundara; R. Fonseka; A. de Abrew; M. S. D. Wijesinghe; H. Senanayake; M. Lazzerini (BMC Research Notes)
Abstract Objective Effective cardiotocography (CTG) training is crucial for accurate interpretation and timely interventions in low-resource settings. This mixed-method study in Sri Lanka developed and assessed an online CTG course to address training gaps and improve neonatal outcomes. The study involved a clinical audit, course development, implementation, and evaluation via the Kirkpatrick model. Results The audit revealed lapses in CTG documentation, interpretation, and interventions. The posttest scores improved by 40.6% (152.8%), but some participants did not complete the course because of a lack of motivation, time constraints, and inadequate facilities. Postimplementation audits revealed improvements in practices, although uterine contraction documentation and overall impression recording declined. The findings suggest the feasibility and effectiveness of online self-learning courses in improving CTG knowledge and practices in Sri Lanka. However, motivation, incentives, and reinforcement measures are needed for better outcomes.